Analysis of Evolution Publications Theme Organizational Justice in Brazil: A Bibliometric Study of the Events ANPAD and SEMEAD - Battistella, Luciana Flores Battistella (2012)
This study aims to conduct a survey on the theme of Organizational Justice and the evolution of their publications over the last 10 years (2001 - 2011), in Brazil, highlighting its relevance in the study of human behavior in organizations. For this, a survey was conducted bibliometric to check the amount of national publications through research in the annals of events (ANPAD and SemeAd) seeking to identify major themes, authors, methodology, sources of title, year of publication, etc.. The research showed that interest in Organizational Justice, in the last decade (2001-2011), is very limited in the number of articles in national events analyzed, cannot be considered a hot topic in national events (m = 1.5). Regarding the theme of Organizational Justice, was not found consensus among researchers about the types and amount of dimensions used for the analysis of the organizational environment. The issue facing the management studies is related to such matters as organizational commitment, job satisfaction, worker health, burnout and consumer behavior more strongly. Thus, the Organizational Justice appears with great respect to matters of organizational behavior, but in Brazil has not attracted much interest from researchers, generating a restricted number of publications on the subject.